Lip repositioning: An alternative cosmetic treatment for gummy smile - Dayakar, Mudnoor Manjunath (Medknow Publications & Media Pvt Ltd, 2014)
Excessive gingival display, commonly referred to as ‘gummy smile’ is a major hurdle in overall personality of an individual. Gummy smile, secondary to altered passive eruption and tooth mal-positioning, can be predictably treated with Surgery and orthodontic therapy. In patients with jaw deformities, orthognathic surgery can be performed. However, this requires hospitalization and entails significant discomfort. Lip repositioning is a simple surgical procedure to treat ‘gummy smile’. The procedure restricts the muscle pull of the elevator lip muscles thereby reducing the gingival display while smiling. This procedure is safe and predictable with minimal risk or side effects. This case report describes the successful treatment of excessive gingival display using surgical lip repositioning procedure which can be used as an alternative treatment modality for treatment of excessive gingival display.